Nursing Diagnoses in Inpatient Psychiatry. Issue 1 (30th November 2014) - Frauenfelder, Fritz; van Achterberg, Theo; Needham, Ian; Müller Staub, Maria
Abstract : Purpose: This study explored how well NANDA‐I covers the reality of adult inpatient psychiatric nursing care. Methods: Patient observations documented by registered nurses in records were analyzed using content analysis and mapped with the classification NANDA‐I. Findings: A total of 1, 818 notes were examined and contained 46 different patient responses. Twenty‐nine patient responses were recognizable as NANDA‐I diagnoses at the level of definitions, 15 as diagnoses‐related factors, and 12 did not match with any NANDA‐I diagnosis. Conclusions: This study demonstrates that NANDA‐I describes the adult inpatient psychiatric nursing care to a large extent. Nevertheless, further development of the classification is important. Implications for Nursing Practice: The results of this study will spur nursing research and further classification development.